Multi-Messenger Astrophysics with THESEUS: Synergies with next generation gravitational wave detectors - Stratta Giulia; Ciolfi Riccardo; Branchesi Marica; Ronchini Samuele; Amati Lorenzo (EPJ Web of Conferences)
Among several breakthrough discoveries in multi-messenger astrophysics achieved in the last decade, there is the first short gamma-ray burst (GRB) associated to the gravitational wave (GW) source GW170817, which confirmed binary neutron star (NS-NS) mergers as short GRB progenitors. More identifications are expected over the next years, but it will only be during the second half of the 2030s that statistically large samples of NS-NS mergers, as well as other GW sources as neutron star-black hole mergers and core collapse supernovae, will become available thanks to the anticipated one order of magnitude increase in sensitivity of next-generation GW detectors. Here we discuss how a gamma/X-ray surveyor like THESEUS will play a crucial role in independently detecting and accurately localizing the electromagnetic counterparts of such GW events, enabling multi-band follow-up campaigns and detailed source characterization of an unprecedented number of multi-messenger sources.